Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c3sm52419a
|View full text |Cite
|
Sign up to set email alerts
|

Cellular self-organization on micro-structured surfaces

Abstract: Micro-patterned surfaces are frequently used in high-throughput single-cell studies, as they allow one to image isolated cells in defined geometries. Commonly, cells are seeded in excess onto the entire chip, and non-adherent cells are removed from the unpatterned sectors by rinsing. Here, we report on the phenomenon of cellular self-organization, which allows for autonomous positioning of cells on micropatterned surfaces over time. We prepared substrates with a regular lattice of protein-coated adhesion sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The use of cells captured on microfluidic- [24] or micro-patterned cell arrays offers a route towards high-throughput analysis. We recently introduced micro-patterned substrates for time-resolved measurements on regularly arrayed cells, and showed that cells self-organize onto fibronectin-coated sites surrounded by boundaries passivated by treatment with poly- l -lysine- polyethylene glycol [25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…The use of cells captured on microfluidic- [24] or micro-patterned cell arrays offers a route towards high-throughput analysis. We recently introduced micro-patterned substrates for time-resolved measurements on regularly arrayed cells, and showed that cells self-organize onto fibronectin-coated sites surrounded by boundaries passivated by treatment with poly- l -lysine- polyethylene glycol [25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Wound healing is a typical biological assay to study collective migration of cells under controlled conditions in vitro and is a prototypical experimental method to study active matter (7)(8)(9)(10). Experiments performed on soluble collagen (11) or other gels (12), micropatterned (13,14) and deformable substrates (1) show that cell migration is guided by the substrate structure and stiffness (5,15,16).…”
mentioning
confidence: 99%
“…In order to test whether the patterns produced are suitable for cell confinement over long timescales, we carried out time-lapse measurements of cells on patterned surfaces over extended time periods. As shown in Fig.S3 of the Supplementary Material (and seen in earlier studies 7,10,39 ), the patterns are stable and capable of confining cells over periods of up to several days.…”
Section: Resultsmentioning
confidence: 87%